Early Fluted-biface Variation in Glaciated Northeastern North America. (3rd April 2019) - Ellis, Christopher J.; Lothrop, Jonathan C.
ABSTRACT: Most researchers argue that archaeological evidence for the Clovis technological complex, although documented across most of unglaciated North America, is absent in the glaciated Northeast, suggesting that early Paleoindian populations in the latter region were descendent from early Native American peoples associated with Clovis technology. If so, what are the earliest fluted-biface forms in glaciated northeastern North America? To refine developmental and relative chronological relationships of early Paleoindian fluted bifaces in the region, we (1) examine fluted-biface-reduction sequences at the Rogers (Ontario) and West Athens Hill (WAH) (New York) sites, and (2) compare fluted-point samples from early Paleoindian sites in the Northeast and vicinity. For Rogers and WAH, our results document variable frequencies of overshot and overface flaking during fluted-point manufacture – features linked elsewhere to Clovis biface reduction. In addition, analyses identify several early Paleoindian fluted-point samples in the Northeast that bear similarities to Clovis points but differ from, and therefore likely predate Gainey and Gainey-related early Paleoindian point forms in the glaciated Northeast.